2016
DOI: 10.1155/2016/8781740
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Immunonutrition on the Postoperative Complications in Thymoma with Myasthenia Gravis

Abstract: Object. To test whether preoperative immunonutrition is efficacious in reducing postoperative complications in patients of thymoma with myasthenia gravis (MG). Material and Methods. A total of 244 patients operated on for thymoma with myasthenia gravis were prospectively assigned to two groups, each receiving seven-day preoperative and seven-day postoperative nutrition. The patients in immunonutrition group were given oral immunonutrition (IN). The patients in control group received oral standard nutrition. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…However, they considered only the clinicopathological characteristics or treatment methods of patients and do not consider relevant hematological indicators. At the same time, many studies on hematological indicators have shown that Hb, NE, LY, platelet (PLT), NLR, ALB, GLB, ALB/GLB, platelet-lymphocyte ratio (PLR), NLR, and SII [12,13,15,25] have potential to become prognostic hematological indicators for various tumors including thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they considered only the clinicopathological characteristics or treatment methods of patients and do not consider relevant hematological indicators. At the same time, many studies on hematological indicators have shown that Hb, NE, LY, platelet (PLT), NLR, ALB, GLB, ALB/GLB, platelet-lymphocyte ratio (PLR), NLR, and SII [12,13,15,25] have potential to become prognostic hematological indicators for various tumors including thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[6,27] In addition, a higher preoperative serum ALB level can often result in a more satisfactory prognosis, which is consistent with the ndings of other studies reporting better prognosis in patients with thymic epithelial tumors with higher ALB levels. [15] In predicting the prognosis of certain cancers, nomograms have been developed and proven to be more accurate than traditional staging systems. [28, 29] Therefore because thymectomy is an effective treatment for thymic epithelial tumors, [30][31][32][33] we constructed a prognostic nomogram for patients with thymic epithelial tumors after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are trials of immunonutrition underway, as well as some results in patients with ovarian, bladder and thymus cancers, but the evidence is still very limited on the effect of immunonutrition in a variety of cancer subtypes 28,43,48 . Different cancer subtypes involve operations of highly variable extent, with their own risks of complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the studies, the duration of follow-up was 30 days after surgery 26,28,32,36,38,41 , 30 days after discharge [20][21][22][23]27,31 or not reported [33][34][35]37,42,43 . In the rest, follow-up was until discharge (median length of hospital stay less than 30 days) 24,25,39,40 , 35 days after surgery 30 or 7 days after surgery 29 .…”
Section: Study Characteristicsmentioning
confidence: 99%